First‐in‐Human Study to Assess the Safety, Tolerability, and Pharmacokinetics of Pirepemat, a Cortical Enhancer, in Healthy Volunteers. Issue 12 (12th June 2021) - Rein‐Hedin, Erik; Sjöberg, Folke; Waters, Susanna; Sonesson, Clas; Waters, Nicholas; Huss, Fredrik; Tedroff, Joakim
Abstract: Pirepemat (IRL752) is a cortical enhancer being developed for the prevention of falls in patients with Parkinson disease. This first‐in‐human, randomized, double‐blind, placebo‐controlled phase 1 study evaluated safety, tolerability, and pharmacokinetics (PK) of pirepemat administered as oral single ascending doses (10, 35, 75, 175, 350 mg) and multiple ascending doses (100 and 250 mg 3 times daily) for 7 days to healthy male volunteers. Twenty and 24 subjects were randomly assigned in the single ascending dose and multiple ascending doses parts of the study, respectively. Pirepemat was generally well tolerated, although an increased frequency of adverse events of mild intensity within nervous system disorders (headache and dizziness) was seen after administration of 350 mg as a single dose and after multiple doses of 100 and 250 mg. PK of pirepemat showed a linear relationship over the dose range studied and exhibited dose proportionality after multiple‐dose administration. Accumulation after 7 days of multiple dosing was minor. Absorption was rapid, with a median time to maximum concentration of 2.0 hours on day 1 and day 7 (100 and 250 mg) and a mean terminal half‐life between 3.7 and 5.2 hours. Food intake had no (obvious) impact on PK. The results support 3‐times‐daily dosing and further clinical development.